Cierpienie i radość w duchowości św. Urszuli Ledóchowskiej - Marcin Godawa (Polonia Sacra)
In St. Urszula Ledóchowska’s thought a question of joy and suffering belongs to the whole relationship between man and God. Following via affective meditation Christ’ life she shows that human and religious problems can be placed in a perspective of heavenly joyfulness to be transformed according to a plan of salvation and a mystery of the Cross. As a consequence the problem of suffering is revaluated in the spirit of supernatural love and next it determines a conception of penance and asceticism. Warned about danger of subjectivism man is called to unite his difficulties and tasks with Jesus to experience plenty of their theological values that is a place of God’s revelation, manifestation of love, a merit, a reward and gladness. The joy is characterized by permanence and independence from outer factors. This attitude of God’s child results in apostolate wherein serenity of soul together with a smile are effective means of Christian witness as well signs of the union with God. The conception of transformed joy and the apostolate of smile make a sanctifying way distinguished by both its depth and attractiveness.